Towards a novel process for milking high value fatty acids from microalgae - Grimsley, Aidan (2022)
The microalga Trachydiscus minutus produces high quantities of eicosapentaenoic acid (EPA), a valuable nutraceutical. However, the slow growing nature of T. minutus and the energy intensive processes of biomass concentration and EPA extraction significantly diminish the economic return of the whole bioprocess. A novel “milking” process, in which EPA can be extracted from cells while retaining their viability, was explored here. This enables repeated extractions from the same cells, reducing the time and energy cost of growing new algal cultures. A literature survey identified two promising milking methods; a biphasic system utilising a water immiscible, biocompatible solvent for product extraction, and pulsed electric fields (PEF) to produce transient pores in the cell membrane. Both methods were applied to dilute cultures, thus bypassing the need to concentrate biomass. The volatile organic compounds typically used in biphasic extractions are often hazardous to the environment and personnel. This project explored the use of water immiscible ionic liquids (ILs), which are salts in the liquid state, as an alternative for biphasic milking. ILs have a vast range of structures and properties, yet their potential in algal milking was relatively unexplored. This project aimed to begin development of EPA milking processes by: (i) identifying solvents, including ILs, which are non-toxic towards T. minutus and could be used in a biphasic milking strategy, (ii) to develop methods for quantifying EPA present in these ILs, and (iii) to explore the ability of PEF to reversibly permeabilise T. minutus cells. A tiered approach was used to screen for non-toxic ILs, using an adapted agar diffusion method, then a small scale liquid toxicity method, and finally a large scale toxicity experiment. This enabled 62 ILs to be screened at significantly reduced costs and time compared to direct large scale experiments. Imidazolium, pyridinium, pyrrolidinium and piperidinium ILs were generally toxic to T. minutus, while results from quaternary ammoniums and phosphoniums were more variable. Trihexyltetradecylphosphonium docusate ([P6 6 6 14][AOT]) and trihexyltetradecylphosphonium bis(2-ethylhexyl)phosphate ([P6 6 6 14][iC8PO4]), were found to be non-toxic to T. minutus, as were the conventional solvents dodecane and tetradecane. These are the first reports of ILs biocompatible with this alga, representing a significant step towards an IL-based biphasic EPA milking strategy for T. minutus. Solvents for an EPA milking strategy must be capable of extracting EPA, so methods for quantifying EPA in ILs were developed. Gas chromatography analysis of fatty acids in conventional solvents is common in the literature. However, this method was deemed unsuitable for analysing non-volatile ILs because they were shown to be introduced into the analytical column, thus restricting flow rate and causing peak broadening. Instead, a HPLC-UV method was developed to enable analysis of liquid samples. This provides a future means to assess the ability of non-toxic ILs to extract EPA from dilute cultures. Using fluorescence staining and flow cytometry analysis, PEF treatments with an electric field strength greater than 3 kV/cm were demonstrated to permeabilise T. minutus. A cell counting method after culture recovery was suitable to assess cell viability after PEF treatment. A commercially available electroporator was unable to treat sufficient volume of T. minutus culture for accurate EPA quantification. A larger PEF chamber design is proposed, to enable treatment of greater volumes in a semi-continuous, more industrially relevant, process. Overall, these findings represent significant progress towards methods for milking EPA from T. minutus and could have applications in wider microbial bioprocesses.